2022
DOI: 10.1021/jacs.2c06584
|View full text |Cite
|
Sign up to set email alerts
|

A Pyridine Dearomatization Approach to the Matrine-Type Lupin Alkaloids

Abstract: +)-Matrine and (+)-isomatrine are tetracyclic alkaloids isolated from the plant Sophora flavescens, the roots of which are used in traditional Chinese medicine. Biosynthetically, these alkaloids are proposed to derive from three molecules of (-)-lysine via the intermediacy of the unstable cyclic imine Δ 1 -piperidine. Inspired by the biosynthesis, a new dearomative annulation reaction has been developed that leverages pyridine as a stable surrogate for Δ 1 -piperidine. In this key transformation, two molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Until very recently, there were three reported total syntheses of (±)-matrine ( 2 ), one synthesis of (+)-allomatrine ( 3 ), and several other syntheses and semisyntheses of related molecules bearing the matrine tetracyclic core . A short time ago, the Reisman group described an elegant synthesis of the matrine framework in racemic form using pyridine as a building block for the B and D rings . This recent publication, which also demonstrates the feasibility of classical resolution, prompts the disclosure of our own approach, which leverages (a) the ability of dendralenes to rapidly generate target-relevant structural complexity (Figure B) and (b) the redox isomerization of amides and amines to drive successive strain-release epimerizations in a tetracyclic framework (Figure C).…”
mentioning
confidence: 97%
“…Until very recently, there were three reported total syntheses of (±)-matrine ( 2 ), one synthesis of (+)-allomatrine ( 3 ), and several other syntheses and semisyntheses of related molecules bearing the matrine tetracyclic core . A short time ago, the Reisman group described an elegant synthesis of the matrine framework in racemic form using pyridine as a building block for the B and D rings . This recent publication, which also demonstrates the feasibility of classical resolution, prompts the disclosure of our own approach, which leverages (a) the ability of dendralenes to rapidly generate target-relevant structural complexity (Figure B) and (b) the redox isomerization of amides and amines to drive successive strain-release epimerizations in a tetracyclic framework (Figure C).…”
mentioning
confidence: 97%
“…8 For example, the ruthenium catalysts (Figure 1a, left) with a chiral diamine ligand promote the highly stereoselective reduction of quinolines, [9][10][11][12] isoquinolines, 13 quinolizidines, 14 benzoxazines, 15 and indoles. 16,17 Hydrogenation of arenes has also been broadly utilized in the total synthesis of natural products, [18][19][20][21] further demonstrating the power of this strategy. Although more and more researchers are devoted to designing homogenous and heterogenous catalysts to achieve the chemo-and stereoselective hydrogenation of aromatic rings, [22][23][24][25][26][27][28][29][30][31][32][33][34][35] the stereoselective perhydrogenation of indole to saturated [6,5]-fused ring system is less explored due to the Synlett Letter / Cluster / New Tools Template for SYNLETT Thieme high energy necessary to break the aromaticity of both pyrrole and benzene ring.…”
mentioning
confidence: 99%
“…8 For example, ruthenium catalysts with a chiral diamine ligand (Figure 1a, left) promote the highly stereoselective reduction of quinolines, [9][10][11][12] isoquinolines, 13 quinolizidines, 14 benzoxazines, 15 and indoles. 16,17 The hydrogenation of arenes has also been broadly utilized in total syntheses of natural products, [18][19][20][21] further demonstrating the power of this strategy.…”
mentioning
confidence: 99%
“…We recently reported the synthesis of isomatrine, matrine, and additional matrine alkaloids using a dearomative annulation reaction of pyridine (10). Mechanistic studies revealed that the cascade cyclization between 10 and glutaryl chloride (8) occurs via a stepwise pathway that could be interrupted by addition of methanol (Scheme 2a).…”
mentioning
confidence: 99%
“…We recently reported the synthesis of isomatrine, matrine, and additional matrine alkaloids using a dearomative annulation reaction of pyridine ( 10 ). Mechanistic studies revealed that the cascade cyclization between 10 and glutaryl chloride ( 8 ) occurs via a stepwise pathway that could be interrupted by addition of methanol (Scheme a). , We hypothesized that if instead of methanol, intermediate 11 could be trapped with 4-pyridone ( 12 ), subsequent enolization and conjugate addition could form the sparteine tetracycle (Scheme b). Unfortunately, initial attempts to trap acid chloride 11 (formed in situ by the reaction of 8 with 10 ) with 2- or 4-pyridone led predominately to O -acylation.…”
mentioning
confidence: 99%